Model Pengembangan Geopark Berbasis Komunitas Goa Boki Maruru (Studi Kasus Desa Sagea Kecamatan Weda Utara) - Nuraini Nuraini,; Marwan Marwan,; Johan Fahri, (Manajemen Kreatif Jurnal, 2023)
The purpose of this study was to identify the management of Goa Boki Maruru, find out the facilities provided for Goa Boki Maruru and develop a model for the development of Goa Boki Maruru. The method in this study was the survey method, namely a research technique through direct observation of a symptom or gathering information through interview guides, questionnaires. The involvement of these various parties can be seen as sufficient in encouraging tourism. However, currently there is no synergy between stakeholders in tourism management activities. Then it has not yet facilitated the management of Boki Maruru tourism as well as regulation and funding as well as assistance and direction. The research results in the FGD also have not found implementation in management activities from the local government as a dimension of Geopark development. In the management development dimension, it was found that there was no monitoring, evaluation, conservation, education and creative economic improvement program from the Government, and there was still a lack of efforts to increase community capacity related to Boki Maruru tourism management. The dimension of developing community-based strengthening shows that there is no transparency and accountability in tourism management due to the lack of basic management and the basics of tourism management by community organizations. It is recommended that the Geopark development model be through: increasing social responsibility, utilizing digital media, increasing community HR cabality, implementing Boki Maruru management training programs for community tourism organizations, and increasing collaboration with academic and private stakeholders.